TEXTURE IMPROVEMENT OF INSTANT TIMPHAN BY LIQUID MODIFICATION OF TIMPHAN DOUGH, GELATINIZATION LEVEL, AND FREEZING TREATMENTS - Dewi Yunita; Nida El Husna; Rinelda ' (Jurnal Sagu, 2013)
Timphan is one of Acehness traditional cakes made from glutinous rice flour and wrapped in banana leaves.It has a short shelf life about 2-3 days. Instanisation of this product could extent the shelf life. This researchwas conducted to improvethe texture of instant timphan through liquid modification of timphan dough, levelof gelatinization and freezing treatments. The instant timphan was then examined by physical, chemical, andsensoryanalysis. The best treatment of instant timphan was found with combination between 1:1 ratio ofgrated coconut and water, 20 minutes steaming and be frozen and this instant timphanhas characteristics asfollows 27.5 minutes of cooking time, 4.33% of cooking loss, and 108.68 g/mm of hardness of timphantexture. According to proximate analysis, this product has 40.10% of water content,26.42% of starch content,3.68% of protein content, 2.87% of fat content, and 0.26% of ash content.Key words: Instant timphan, liquid modification, level of gelatinization, freezing treatment.